Pengaruh Resonansi Terhadap Perubahan Efisiensi Perangkat Oscillating Water Column (OWC) - Jahirwan Ut Jasron (Jurusan Teknik Mesin, Fakultas Sains dan Teknik, Universitas Nusa Cendana, 2021)
Oscillating water column (OWC) is the most promising wave energy converter to be applied because of its simple mechanical structure. To achieve maximum energy conversion efficiency, the device structure's incident wave frequency and natural frequency must be resonant. This paper discusses several factors that cause resonance, such as the incident wave period and the comparison of the length of the submerged front wall with the size of the inlet opening (a/c) and their effect on the efficiency of the OWC. The test results explain a resonance condition in which the a/c ratio of 0.67 in the wave period of 1.3 s produces a maximum efficiency of 24.13%.